Cross Country Canada's business plan 2013/14 (2013)
Cross Country Canada`s Business Plan l 2013/14 Contents: PRESIDENT`S PERSPECTIVE EXECUTIVE DIRECTOR`S OVERVIEW REPORT ON PERFORMANCE 2012/13 2013/14 REVENUE OUTLOOK OPERATIONAL PLAN 2013/14 • HIGH PERFORMANCE OPERATIONAL PLAN 2013/14 • PARA-NORDIC OPERATIONAL PLAN 2013/14 • COACH AND ATHLETE DEVELOPMENT OPERATIONAL PLAN 2013/14 • WOMEN`S COMMITTEE OPERATIONAL PLAN 2013/2014 • MARKETING AND FUNDRAISING OPERATIONAL PLAN 2013/14 • ADMINISTRATION AND COMMUNICATIONS OPERATIONAL PLAN 2013/14 • EVENTS OPERATIONAL PLAN 2013/14 NATIONAL SKI TEAMS AND COACHING STAFF 2013/14 STRATEGIC PLAN TO 2018+ "IT`S OUR TIME!" (EXCERPTS)